A new species of Philodendron (Araceae) associated with quartzite-derived outcrops in Southeastern Brazil - Magno, Alexandre; Faller, Vagner S.; Mortara, Marcos; Calazans, Luana S.b.; Sakuragui, Cassia M. (Phytotaxa, 2025)
Here we describe Philodendron quartziticola, a new species of Araceae from the Atlantic Forest of Espírito Santo, Southeastern Brazil. The species is commonly associated with quartzitic substrates, in addition to environments locally referred to as “Morros de Sal”, which are characterized by saccharoidal quartzite formations. Morphological comparisons with closely related taxa are provided to delimit the new species, as well as photographic plates, field images, and a distribution map to document its morphology and range. This discovery is particularly relevant due to the species’ occurrence in environments heavily impacted by mineral extraction and land-use change.